Mother and child narrative elaborations during booksharing in low‐income Mexican‐American dyads. Issue 6 (16th March 2017) - Escobar, Kelly; Melzi, Gigliana; Tamis‐LeMonda, Catherine S.
Abstract: Caregivers' narrative elaborations have been consistently shown to relate to language, literacy, and cognitive skills in children. However, research with Latinos yields mixed findings in terms of how much caregivers elaborate and the benefits of elaborations for Latino children's development, especially within booksharing contexts. Moreover, little research has investigated whether and how children elaborate, and whether individual differences among children's narrative elaborations are related to changes in maternal elaborations over time. The current longitudinal study describes specific types of elaborations used by children and mothers and examines reciprocal relations between children's and mothers' elaborations over 1 year (at child age 3 and child age 4), in a sample of 45 Mexican immigrant mothers and their preschool‐aged children. Maternal elaborations positively related to children's narrative development only when subtypes of elaborations were considered, but not when considering the frequency of elaborations more broadly. Moreover, children's elaborations at age 3 were differentially associated with specific maternal elaborations a year later. Findings underscore the need to examine narrative elaborations at a nuanced level in Latino populations. Highlights: This paper examines the specific ways in which Latino dyads elaborate during booksharing interactions Dyads were video recorded sharing a wordless picture book at two time points over 1 year. Findings suggest that specific elaboration types, namely, dyadic forms of responses and requests, are most important for the development of concurrent narrative skills, even though they are the least frequently used in this context We conclude that the investigation of narrative elaborations needs to be approached at a more nuanced level when studying Latino populations, as there are various roles taken and behaviors expected when changing the narrative context. These findings have implications for the development of culturally appropriate interventions targeted at enhancing booksharing practices with Latino groups